Combining beams in different locations for aerospace defense in a turbulent atmosphere - Liao, Kangjie; Liu, Zhiwei; Chu, Xiuxiang (Frontiers in Physics, 2022)
A fixed high-power laser system used as aerospace defense weapon has the limitation of transmitter size, serious thermal blooming during propagation, rapid motion and the variation of the location of target. In present paper we propose a method by arranging many high-power systems with adequate distance in a defense area. The intensity distribution and the energy irradiated on the target are studied and compared with a fixed laser system. Result shows that adequate arrangement of many high-power laser systems can reply the arbitrary and rapid motion of the target.